THE VALID SPECIES AND DISTRIBUTION OF STINGRAYS (Myliobatiformes: Dasyatidae) IN SOUTH SUMATERA WATERS, INDONESIA - Iqbal, Muhammad; Zulkifli, Hilda; Yustian, Indra (BIOVALENTIA: Biological Research Journal, 2018)
A recent study to providing valid checklist of stingrays species in South Sumatran waters provide 14 species: Brevitrygon heterura, Fluvitrygon kittipongi, Fluvitrygon oxyrhyncha, Fluvitrygon signifier, Fluvitrygon sp ‘musi’ 1, Fluvitrygon sp ‘musi’ 2, Himantura undulata, Himantura uarnak, Maculabatis gerrardi, Pateobatis fai, Pateobatis uarnacoides, Pastinachus ater, Telatrygon biasa  and Urogymnus polylepis. Distributional patterns of stingrays in South Sumatran waters are depend on species or (at least) genus level. Stingrays in South Sumatran waters are recorded from of up to more 100 km inland to the coastal zone area. Following IUCN Red List status, 10 species of stingrays are threatened with status Endangered, Vulnerable and Data Deficient; suggest the South Sumatran waters are important habitat for stingrays in Indonesia.